2019
DOI: 10.3988/jcn.2019.15.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chemotherapy-Induced Peripheral Neuropathy in Patients with Lymphoma and Myeloma: the Roles of Brain-Derived Neurotropic Factor Protein Levels and A Gene Polymorphism

Abstract: Background and PurposeBrain-derived neurotrophic factor (BDNF) is a neuronal growth factor that plays an essential role in the maintenance of the nervous system. We have evaluated the peripheral blood protein levels of BDNF and the valine-to-methionine substitution at codon 66 (Val66Met) single-nucleotide polymorphism (SNP) as potential biomarkers for the early recognition of chemotherapy-induced peripheral neuropathy (CIPN) in non-Hodgkin lymphoma and multiple myeloma patients.MethodsCIPN was assessed in 45 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…The authors showed that the BDNF concentration before treatment was inversely proportional to the results of the TNSr, FACT‐GOG‐NTx and PHQ‐9 scales in both genotypes. Carriers of the Val/Val genotype had significantly higher FACT‐GOG‐NTx and PHQ‐9 results compared to patients with the Val/Met and Met/Met genotypes (Met‐BNDF carriers) 24 . In our study, we showed a relationship (positive correlation) between serum BDNF concentration before treatment and the severity of CTCAEv5.0 assessed polyneuropathy in MM patients undergoing chemotherapy with thalidomide or bortezomib ( ρ = 0·507; P = 0·0001).…”
Section: Discussionsupporting
confidence: 48%
“…The authors showed that the BDNF concentration before treatment was inversely proportional to the results of the TNSr, FACT‐GOG‐NTx and PHQ‐9 scales in both genotypes. Carriers of the Val/Val genotype had significantly higher FACT‐GOG‐NTx and PHQ‐9 results compared to patients with the Val/Met and Met/Met genotypes (Met‐BNDF carriers) 24 . In our study, we showed a relationship (positive correlation) between serum BDNF concentration before treatment and the severity of CTCAEv5.0 assessed polyneuropathy in MM patients undergoing chemotherapy with thalidomide or bortezomib ( ρ = 0·507; P = 0·0001).…”
Section: Discussionsupporting
confidence: 48%
“…One study found a higher rate of suicide in cancer patients carrying the Met allele 25 . Interestingly, several recent studies provided new evidence to suggest a protective role of Val66Met against chemotherapy-induced cognitive impairment and depression 26 28 . In addition, Val66Met is a particularly interesting candidate SNP to examine for cancer-related fatigue due to the well-established symptomatic and possible mechanistic overlap between fatigue and depression 29 , and for the profound influence Val66Met has on the risk of depression in otherwise healthy individuals 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism could be the alteration of neurotrophic factors by chemotherapy administration that are important in the maintenance and repair of the central and peripheral nervous system. Brain derived neurotrophic growth factor levels have been implicated in both Dep/Anx in individuals with CIPN where lower levels are correlated with increased depression, anxiety, and CIPN in lymphoma and multiple myeloma patients [32][33]. It is biologically plausible that chemotherapy could alter levels of circulating brain derived neurotrophic growth factor and may contribute to both CIPN as well as depression and/or anxiety in BrCa survivors.…”
Section: Discussionmentioning
confidence: 99%